Students’ Mathematical Creative Thinking Ability in LAPS-Heuristic Learning Model with Performance Assessment and Open-Ended Questions - Agustina, Vena; Fashihah, Fashihah; Relitasari, Puput; Apriliana, Nurani; Khumairo', Siti Latifatul (Universitas Islam Sultan Agung, 2025)
This quantitative research with a quasi-experimental design demonstrates several significant findings regarding the quality of LAPS-Heuristic learning with performance assessment and open-ended questions of students' Mathematics’ Creative Thinking Ability (MCTA): (1) In the planning phase, the validation of learning materials and research instruments was classified as at least satisfactory; (2) During the implementation phase, the quality assessment sheets from the first to the third meetings were as at least satisfactory; (3) Student's response to LAPS-Heuristic learning combined with performance assessment and open-ended questions was notably positive, achieving a rating of 70.75%, which is categorized as strong; and (4) During the assessment stage, the results obtained from the LAPS-Heuristic learning combined with performance assessment and open-ended questions, indicate several notable findings concerning students' MCTA. First, the completion rate for students engaged in LAPS-Heuristic learning combined with performance assessment and open-ended questions surpassed 75%. Second, the average of students' MCTA who participated in LAPS-Heuristic learning, combined with performance assessment and open-ended questions, demonstrated significant improvement compared to those who participated in LAPS-Heuristic learning. Third, the proportion of experiment class students exhibiting stronger MCTA than the control class students. Keywords: MCTA, LAPS-Heuristic, Performance Assessment, Open-Ended.